El ciclo presupuestario político y el endeudamiento: un estudio en los municipios de la zona 3 de Ecuador - Guilcapi Ushca, Ery Fabricio (2026)
The political budget cycle is understood as the set of fiscal decisions that governments adopt under the influence of election cycles, which can modify the allocation of public resources and the use of debt. At the municipal level, this behavior is particularly relevant, as local governments operate with budgetary constraints, dependence on transfers, and high levels of political pressure. In this context, variables such as debt, spending rigidity, capital expenditure, and financial autonomy allow for a more precise understanding of how fiscal dynamics are configured in these territories. This research employed a quantitative approach based on an econometric panel data model, which combines temporal and cross-sectional information from the municipalities of Zone 3 of Ecuador. This design allowed for a more in-depth analysis of both the structural differences between municipalities and the effects associated with the electoral cycle and the political leanings of local governments. The databases used are sourced from official sources, including the Ministry of Economy and Finance, municipal budget schedules, and the National Electoral Council. The analysis revealed that electoral and pre-electoral periods are associated with a significant increase in municipal debt, a finding that persists even after controlling fiscal and institutional variables. Finally, the findings also show that financial autonomy acts as a protective factor against this behavior, while spending rigidity and certain investment patterns intensify debt pressure. These results demonstrate the presence of a political budget cycle in the region.